2004
DOI: 10.1007/s00198-004-1771-6
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative ultrasound and dual-energy X-ray absorptiometry in the prediction of fragility fracture in men

Abstract: Fragility fractures in men represent a major health problem, and this prompts a necessity for reliable tools for the identification of men at risk of fracture. In order to assess the ability of dual-energy X-ray absorptiometry (DXA) and quantitative ultrasound (QUS) in the prediction of fracture risk in men and whether their combination might be useful in a clinical setting, we studied 401 men (age range 45-82 years, mean 60.3+/-12.5), of whom 133 had osteoporotic fractures and 268 did not. In all subjects we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
42
1
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(50 citation statements)
references
References 31 publications
5
42
1
2
Order By: Relevance
“…While the associations between bone turnover and QUS tended to be slightly weaker than with DXA, findings were consistent across different skeletal sites and across different assessment methods, supporting the concept that QUS measurements in calcaneal bone should be primarily regarded as an indicator of bone density (66). In line with this concept, QUS parameters and DXA-assessed BMD a have been shown to be equally predictive for incident fractures, in both sexes (67)(68)(69).…”
Section: Discussionsupporting
confidence: 51%
“…While the associations between bone turnover and QUS tended to be slightly weaker than with DXA, findings were consistent across different skeletal sites and across different assessment methods, supporting the concept that QUS measurements in calcaneal bone should be primarily regarded as an indicator of bone density (66). In line with this concept, QUS parameters and DXA-assessed BMD a have been shown to be equally predictive for incident fractures, in both sexes (67)(68)(69).…”
Section: Discussionsupporting
confidence: 51%
“…Cummings et al [24] also found that high physical activity was an independent protective factor against hip fracture. In 45-82-year-old men, heel broadband ultrasound attenuation (BUA) assessed using quantitative ultrasound (QUS), has been associated with fragility fractures [36]. Furthermore, it was recently reported in a study in adolescent males that prevalent upper limb fractures were associated with reduced calcaneal BUA [37].…”
Section: Discussionmentioning
confidence: 99%
“…While DXA measures bone mass, BMD, and BMC [31], QUS provides information on bone microarchitecture and strength [32]. The different aspects of bone health covered by DXA or QUS produce complementary information on a patients bone status and might be independently linked to osteoporosis and fracture risk [33]. Thus, a low DXA or QUS result corresponds to a high fracture risk [30].…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, it is well accepted that low BMI is associated with high osteoporosis prevalence and high risk for self-reported and radiologically verified fractures [10,21]. Among the QUS parameters, stiffness index provides the best validity to estimate fracture risk [33]. Apart from stiffness index, other parameters including fall history and clinical risk factors contribute to the individual risk for fragility fracture [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation